Value of Life, Value of Time, and Constant Relative Risk Aversion Utility. - Allan M. Feldman (Brown University, Department of Economics, 1998)
This paper develops two straightforward value of life models; one is a probabilistic value of life model and the second is a determinstic value of time model. Simplifying assumptions allow both models to be solved analytically. Constant relative risk aversion utility functions are used, and both value of life and value of time are solved for a functions of the relative risk-aversion parameter.
Keywords: D11; D61; D60; D91; 330